STUDY OF CHINESE LANGUAGE SERVICE OF THE EMQUARTIER DEPARTMENT STORE - BORIBOON, WATCHAREE (Chinese Language and Culture Journal, 2020)
Nowadays Thailand has become a top destination for tourists from around the world, especially the Chinese. We have seen increasing numbers of Chinese tourists visiting Thailand. Tourist attractions are not their only traveling propose. The research shows that when they visit Bangkok, they spend most of their travel expenses on food and shopping. For this reason, many department stores in the city offer special services for Chinese tourists – including “The EmQuartier” which focuses on high spenders. It was opened on 27th March 2015 as one of the largest shopping complexes. Its luscious rooftop garden and outdoor waterfall have since become Bangkok’s landmarks. In 2017, The EmQuartier was awarded Chinese People’s Choice Awards Thailand of that year, which attests to its popularity among Chinese visitors. The main focus of this thesis is to study the marketing models and strategies of The EmQuartier, and to assess the quality of Chinese-language services, for example, tourist centers, shops, website, etc. It also aims to evaluate the satisfaction of Chinese tourists through quantitative and qualitative analysis of questionnaire survey. Especially explains the marketing model and general services for Chinese tourists provided at the mall and Chinese services will be explored and analyzed in detail. Including will summarize all the findings regarding the marketing and Chinese-language services. The research found that in terms of quality, 41% of Chinese language services in this department store is quite poor. 55% of Chinese service staff still has many problems. The EmQuartier needs to upgrade the quality of its Chinese language service to meet the needs of Chinese tourists who visit in the department store. The thesis also points out current issues and proposes suggestions to improve the Chinese language services, which I hope will be useful in the future.